The North Pole to Greenland: A Scientific Transect - McCallum, A B (University of the Sunshine Coast, 2012)
In April 2012 a team of four set out south from the North Pole, their destination: Greenland, over 700 km away; their aim: the intimate collection of never-before obtained data from beneath the ice; data that could verify the role that a changing Arctic may play in the greater Atlantic circulation, with implications for the climate of Europe and beyond. That was the 2011 Catlin Arctic Survey, and I was one of that team. The aim of the 2011 Catlin Arctic Survey was to investigate how changes in the Arctic Ocean may impact the Atlantic thermohaline circulation; a global ocean circulation system that affects climate and weather patterns worldwide, driven by buoyancy differences because of changes in water temperature and salinity. Diminished extent and thickness of sea ice, thawing permafrost and increased rainfall and runoff from glaciers and rivers is increasing the amount of freshwater entering the Arctic Ocean; temperatures are rising and these processes may interrupt the driving and sinking mechanisms of Atlantic surface water. The expedition phase of the Survey consisted of a six-week overland traverse from the vicinity of the North Pole towards Greenland. The scientific routine included observations of sea ice morphology, measurement of ocean temperature and salinity to hundreds of metres beneath the ice and three-dimensional profiling of currents to a depth of 100 m. Measurements were obtained daily after manually drilling through the sea ice, sometimes in temperatures less than -50oC. Although preliminary analysis has occurred, the wealth of data obtained throughout this innovative survey are still undergoing scrutiny. The 2011 Catlin Arctic Survey was an audacious privately-funded research expedition, the results of which may shed new light on evolving climates within a changing world.